PENGARUH KETIDAKLURUSAN DAN KETIDAKSIMETRISAN PEMASANGAN SIRIP PADA PRESTASI TERBANG ROKET RX-250-LPN - Atmadi, Sulistyo; Riyadi, Ahmad (Indonesian Journal of Aerospace, 2003)
The performance of a rocket depend on several factor, one of which is the value of drag experienced during flight. This drag is contributed by the shape and the many components of the rocket. This paper discussed the fin misalignment and asymetrisness in respect to its main axis, which results in a change in the drag of RX-250-LPN rocket. The discussion was conducted with assuming the variation of this fin alignment from 1 degree to 2 degree. DATCOM was used to obtain aerodynamic parameters of the rocket. In addition, MATLAB 6.3 was used to calculate the performance of rocket. The knowledge of this fin misalignment can be used to get the minimum accuracy needed for better fin setting during rocket assembly.